Harga Diri dan Religiusitas dengan Resiliensi Pada Remaja Madura Berdasarkan Konteks Sosial Budaya Madura - Rahmasari, Diana; Jannah, Miftakhul; Puspitadewi, Ni Wayan Sukmawati (Jurnal Psikologi Teori dan Terapan, 2014)
Madurese known by the sense of self-esteem "typical" as "âajina abhaâ" as well as a strong religiosity and synonymous with Islam. Needed to strengthen the resilience of youth in the face of obstacles or problems. This study is a preliminary study aimed to examine the dynamics of the relationship between self-esteem and religiosity with resilience in adolescents. This research is using quantitative methods. Quantitative methods are used to examine the relationship between self-esteem and religiosity with resilience. The results showed that there is a relationship between self-esteem and religiosity with resilience in adolescents Madura with a value of 0.01. Self-esteem and religiosity together to give effect to the resilience of 16.9%. This means that 83.1% of resilience in adolescents Madura is influenced by other variables. Esteem gives greater influence with significant value 0,311. While religiosity effect of 0.264. It can be concluded that self-esteem and religiosity have an influence on adolescents resilience in Madura.